Alport's syndrome - Bastola, P; Joshi, SN; Chaudhary, M; Shah, DN (Kathmandu University Medical Journal, 2010)
Alport's syndrome (Haemorrhagic Familial Nephritis) is a rare syndrome. It encompasses a group of heterogeneously inherited disorders involving the basement membrane of the kidney frequently involving the cochlea and the eye. We describe here the detailed ocular findings and the systemic problems of a case of Alport's syndrome in a 30 years male from Nepal. The current understanding of the clinical features and aetiopathogenesis are also discussed. Key words: Alport's syndrome; Anterior lenticonus; Oil droplet sign; Anterior capsular cataract; Perimacular flecks DOI: 10.3126/kumj.v8i2.3566 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 238-240